Electrochemical devices and electronic devices

By using a first coating with moderate carbon nanotube content in the negative electrode sheet of the electrochemical device and combining the second coating, the problem of difficult to take into account both impact resistance and energy density in the prior art is solved, and more efficient electrochemical performance is achieved.

CN115516662BActive Publication Date: 2025-04-22NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180031502.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-11
Publication Date
2025-04-22
Estimated Expiration
2041-11-11

AI Technical Summary

Technical Problem

While improving the circulation performance and energy density, existing electrochemical devices are difficult to take into account both impact resistance, especially if the excessive coating thickness will affect the increase of energy density.

Method used

Using a first coating with a mass content of 50% to 75%, combined with the binder and dispersant in the first and second coatings, the coating thickness is controlled between 200 nm and 2 μm to improve the bonding force between the negative electrode current collector and the active material layer.

Benefits of technology

By optimizing the coating structure, the impact resistance of the electrochemical device is improved, while the overall electrical performance of the electrochemical device is improved without damaging the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115516662B_ABST
    Figure CN115516662B_ABST
Patent Text Reader

Abstract

The present application provides an electrochemical device and an electronic device. The electrochemical device includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector, a first coating and a negative electrode active material layer, and the first coating is arranged between the negative electrode current collector and the negative electrode active material layer. The first coating includes carbon nanotubes, a first binder and a first dispersant, and the mass content of the carbon nanotubes in the first coating is 50% to 75%. The embodiments of the present application help to improve the impact resistance of the electrochemical device by using a first coating with a mass content of carbon nanotubes of 50% to 75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrochemical devices and electronic devices. Background Art

[0002] With the development and progress of electrochemical devices (e.g., lithium-ion batteries), higher and higher requirements are put forward for their cycle performance, energy density and safety performance. At present, in order to improve the cycle performance of electrochemical devices, a coating is usually provided between the negative current collector and the negative active material layer of the negative electrode sheet to enhance the bonding force between the negative current collector and the negative active material layer. However, the thickness of the coating is relatively large, usually greater than 2 μm, which is not conducive to the improvement of the energy density of the electrochemical device, so further improvements are expected. Summary of the invention

[0003] Some embodiments of the present application provide an electrochemical device, the electrochemical device includes a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector, a first coating and a negative electrode active material layer, the first coating is arranged between the negative electrode current collector and the negative electrode active material layer. The first coating includes carbon nanotubes, and the mass content of the carbon nanotubes in the first coating is 50% to 75%.

[0004] In some embodiments, the first coating further includes a first binder and a first dispersant, the mass content of the first binder in the first coating is 25% to 45%, and the mass content of the first dispersant in the first coating is greater than 0 and less than or equal to 5%.

[0005] In some embodiments, the first coating has a thickness of 200 nm to 2 μm. In some embodiments, the first coating has a thickness of 800 nm to 1 μm.

[0006] In some embodiments, the diameter of the carbon nanotubes is 2 nm to 2000 nm.

[0007] In some embodiments, under Raman spectroscopy, the carbon nanotubes have D / I G The ratio is greater than 1.4.

[0008] In some embodiments, under Raman spectroscopy, the carbon nanotubes have D / I G The ratio is less than or equal to 1.7.

[0009] In some embodiments, the electrochemical device further comprises a second coating, the negative electrode active material layer is located between the first coating and the second coating, the second coating comprises carbon nanotubes, and the mass content of the carbon nanotubes in the second coating is 50% to 75%.

[0010] In some embodiments, the second coating further includes a second binder and a second dispersant, the mass content of the second binder in the second coating is 25% to 45%, and the mass content of the second dispersant in the second coating is greater than 0 and less than or equal to 5%.

[0011] In some embodiments, the thickness of the second coating layer is greater than 0 and less than or equal to 450 nm.

[0012] In some embodiments, the first binder and the second binder each independently include at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyacrylate, or polyacrylonitrile.

[0013] In some embodiments, the first dispersant and the second dispersant each independently include at least one of sodium hydroxymethylcellulose, lithium hydroxymethylcellulose, or N-methylpyrrolidone.

[0014] In some embodiments, the resistance of the negative electrode plate is 90 mΩ to 1000 mΩ.

[0015] An embodiment of the present application further provides an electronic device, comprising any of the above-mentioned electrochemical devices.

[0016] The embodiments of the present application help improve the impact resistance of the electrochemical device by using a first coating layer with a carbon nanotube content of 50% to 75% by mass. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic cross-sectional view of a negative electrode sheet in the width direction according to some embodiments of the present application is shown.

[0018] Figure 2 Schematic cross-sectional views of negative electrode sheets in the width direction according to other embodiments of the present application are shown. DETAILED DESCRIPTION

[0019] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0020] Some embodiments of the present application provide an electrochemical device, the electrochemical device comprising a negative electrode sheet. Figure 1 , which shows a schematic cross-sectional view of a negative electrode sheet 10 in the width direction according to some embodiments. The negative electrode sheet 10 includes a negative electrode current collector 101, a first coating 102 and a negative electrode active material layer 103, wherein the first coating 102 is disposed between the negative electrode current collector 101 and the negative electrode active material layer 103. It should be understood that although the first coating 102 and the negative electrode active material layer 103 are Figure 1101 is shown as being located only on one side of the negative electrode collector 101 , but this is merely exemplary, and the negative electrode active material layer 103 may be located on both sides of the negative electrode collector 101 , and the first coating layer 102 may separate the negative electrode active material layer 103 on both sides from the negative electrode collector 101 .

[0021] In some embodiments, the first coating 102 includes carbon nanotubes. In some embodiments, the carbon nanotubes may include at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes. In some embodiments, the mass content of the carbon nanotubes in the first coating is 50% to 75%. In some embodiments, the first coating 102 also includes a first binder and a first dispersant, the mass content of the first binder in the first coating 102 is 25% to 45%, and the mass content of the first dispersant in the first coating is greater than 0 and less than or equal to 5%. By using carbon nanotubes (CNT) in the first coating 102, the conductive mode of CNT is tube wall conductivity, so that the resistance of the first coating 102 is relatively large. During normal charging and discharging, electrons continue to pass in the direction of the tube wall to form a stable power supply. The apparent DC resistance (DCR) is slightly lost, and other properties are normal. During the impact safety performance test, the electrochemical device is short-circuited at the moment when the round rod is smashed. Usually, a huge amount of electrons pass through, generating huge heat, causing the electrochemical device to burn. However, since the CNT is conductive through the tube wall and has a long path, the huge electron flow cannot immediately pass through the CNT to cause a large amount of heat generation and runaway conditions. At the moment when the round rod is smashed, the current density on the negative electrode current collector 101 is low, thereby reducing heat accumulation and improving impact resistance. When the mass content of the carbon nanotubes in the first coating 102 is less than 50%, it will affect the electrical properties of the first coating 102, which is not conducive to the improvement of the overall electrical properties of the electrochemical device. When the mass content of the carbon nanotubes in the first coating 102 is greater than 75%, on the one hand, the mass content of the carbon nanotubes is too high, which will reduce the mass content of the binder, which is not conducive to the stable bonding between the negative electrode current collector 102 and the negative electrode active material layer 103; on the other hand, the mass content of the carbon nanotubes is too high, and when the electrochemical device is impacted, the huge electron flow can still be out of control through the CNT to generate a large amount of heat, which is not conducive to the improvement of the impact resistance of the electrochemical device.

[0022] In some embodiments, the thickness of the first coating 102 is 200nm to 2μm, and the thickness described here and below refers to the average thickness. When the thickness of the first coating 102 is too small, it is not conducive to the stable bonding between the negative electrode current collector 102 and the negative electrode active material layer 103. When the thickness of the first coating 102 is too large, it is not conducive to the improvement of the energy density of the electrochemical device. In some embodiments, the thickness of the first coating 102 is 800nm ​​to 1μm. In this way, stable bonding between the negative electrode current collector 102 and the negative electrode active material layer 103 can be achieved, and the adverse effect on the energy density of the electrochemical device can be minimized.

[0023] In some embodiments, the diameter of the carbon nanotubes is 2nm to 2000nm. If the diameter of the carbon nanotubes is too large, the thickness of the first coating 102 is usually required to be relatively large, which is not conducive to the improvement of the energy density of the electrochemical device, nor is it conducive to the improvement of the electrical performance of the electrochemical device. If the diameter of the carbon nanotubes is too small, the path of the current in the carbon nanotubes will be reduced, and the effect of the carbon nanotubes in improving the impact resistance will be lost. In some embodiments, the diameter of the carbon nanotubes is 2nm to 200nm. In this way, the effect of improving the impact resistance of the electrochemical device can be achieved, and the adverse effect on the energy density of the electrochemical device can be minimized.

[0024] In some embodiments, the carbon nanotubes have a Raman spectroscopy test result of D / I G The ratio is greater than 1.4. D Indicates 1350cm in Raman spectrum -1 The peak intensity at I G Indicates 1580cm in Raman spectrum -1 The peak intensity at I D / I G The ratio of I reflects the graphitization degree of CNT. D / I G The larger the ratio of , the lower the degree of graphitization, and the greater the defects of the CNT structure. In order to minimize the loss of the initial efficiency of the electrochemical device, the graphitization degree of the CNT is reduced to reduce the lithium insertion performance of the CNT, so as to alleviate the reduction of the initial efficiency of the electrochemical device. In some embodiments, under Raman spectroscopy, the I D / I G The ratio is less than or equal to 1.7. For example, the I D / I G The ratio can be 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, etc.

[0025] In some embodiments, Figure 2 As shown, the negative electrode sheet 10 further includes a second coating layer 104, and the negative electrode active material layer 103 is located between the first coating layer 102 and the second coating layer 104. It should be understood that although Figure 2Only the first coating 102, the negative electrode active material layer 103, and the second coating 104 on one side of the negative electrode current collector 101 are shown, but the first coating 102, the negative electrode active material layer 103, and the second coating 104 may also be provided on the other side of the negative electrode current collector 101, and the corresponding layers may be symmetrically arranged about the negative electrode current collector 101. In some embodiments, the second coating 104 includes carbon nanotubes. In some embodiments, the carbon nanotubes may include at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes. In some embodiments, the mass content of the carbon nanotubes in the second coating 104 is 50% to 75%. In some embodiments, the second coating 104 also includes a second binder and a second dispersant, the mass content of the second binder in the second coating 104 is 25% to 45%, and the mass content of the second dispersant in the second coating is greater than 0 and less than or equal to 5%. The second coating 104 can further improve the impact resistance of the electrochemical device. The relevant principle description is referred to the description of the first coating 102, which will not be repeated here.

[0026] In some embodiments, the thickness of the second coating 104 is greater than 0 and less than or equal to 450nm, and the thickness described here and below refers to the average thickness. If the thickness of the second coating 104 is too large, it is not conducive to the improvement of the energy density of the electrochemical device. In some embodiments, the thickness of the second coating 104 is greater than or equal to 50nm and less than or equal to 350nm. In some embodiments, the thickness of the second coating 104 is greater than or equal to 100nm and less than or equal to 250nm. In this way, a better balance between the impact resistance and energy density of the electrochemical device can be achieved.

[0027] In some embodiments, the first binder and the second binder each independently include at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyacrylate or polyacrylonitrile. In some embodiments, the first dispersant and the second dispersant each independently include at least one of sodium hydroxymethylcellulose, lithium hydroxymethylcellulose or N-methylpyrrolidone.

[0028] In some embodiments, the resistance of the negative electrode plate 10 is 90 mΩ to 1000 mΩ. If the resistance of the negative electrode plate 10 is too small, it is not conducive to improving the impact resistance of the electrochemical device. If the resistance of the negative electrode plate 10 is too large, it is not conducive to improving the rate performance of the electrochemical device.

[0029] In some embodiments, the negative electrode active material layer may include a negative electrode active material, a conductive agent, and a binder. In some embodiments, the negative electrode active material may include at least one of graphite, silicon, silicon oxygen, or silicon carbon. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, Ketjen black, flake graphite, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the binder in the negative electrode active material layer may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin, or polyfluorene. In some embodiments, the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode active material layer may be (78 to 98.5): (0.1 to 10): (0.1 to 10). It should be understood that the above is only an example, and any other suitable material and mass ratio may be used. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil, or a carbon-based current collector.

[0030] In some embodiments, the electrochemical device may include an electrode assembly, the electrode assembly including a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. In some embodiments, the negative electrode sheet is any of the negative electrode sheets described above.

[0031] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte solution.

[0032] In some embodiments, the electrolyte includes at least one of fluoroether, fluoroethylene carbonate or ether nitrile. In some embodiments, the electrolyte also includes a lithium salt, the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, the concentration of the lithium salt is 1 mol / L to 2 mol / L, and the molar ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is 0.05 to 4.

[0033] In some embodiments, the electrolyte may further include a non-aqueous solvent, which may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents, or a combination thereof.

[0034] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0035] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0036] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0037] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0038] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0039] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, and the positive active material layer may include a positive active material. In some embodiments, the positive active material includes at least one of lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadate, lithium manganate, lithium nickelate, lithium nickel cobalt manganate, lithium-rich manganese-based materials, or lithium nickel cobalt aluminum oxide. In some embodiments, the positive active material layer may also include a conductive agent. In some embodiments, the conductive agent in the positive active material layer may include at least one of conductive carbon black, ketjen black, lamellar graphite, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the positive active material layer may also include a binder, and the binder in the positive active material layer may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin, or polyfluorene. In some embodiments, the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode active material layer may be (80 to 99): (0.1 to 10): (0.1 to 10). In some embodiments, the thickness of the positive electrode active material layer may be 10 μm to 500 μm. It should be understood that the above description is only an example, and the positive electrode active material layer may adopt any other suitable material, thickness, and mass ratio.

[0040] In some embodiments, the positive electrode current collector may be Al foil, and of course, other current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 50 μm. In some embodiments, the positive electrode active material layer may be coated only on a partial area of ​​the current collector of the positive electrode sheet.

[0041] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 50 μm.

[0042] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.

[0043] In some embodiments of the present application, the electrode assembly of the electrochemical device is a wound electrode assembly, a stacked electrode assembly, or a folded electrode assembly. In some embodiments, the positive electrode sheet and / or the negative electrode sheet of the electrochemical device can be a multi-layer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.

[0044] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode, a separator, and a negative electrode are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.

[0045] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.

[0046] Embodiments of the present application also provide an electronic device including the above-mentioned electrochemical device. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0047] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0048] Example 1

[0049] Preparation of positive electrode:

[0050] The positive electrode active material lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 97.5:1:1.5, and N-methylpyrrolidone (NMP) was added as a solvent and stirred evenly. The slurry (solid content of 75wt%) was evenly coated on a 10μm positive electrode current collector aluminum foil with a coating thickness of 80μm, dried at 85°C, and then cold pressed, cut, and slit, and dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode sheet.

[0051] Preparation of negative electrode sheet:

[0052] 64.5wt% CNT, 32.3wt% PVDF and 3.2wt% sodium carboxymethyl cellulose were placed in a stirring tank and dispersed evenly, and a certain amount of deionized water was added to accelerate the dispersion. The slurry was coated on a 6μm Cu foil using a gravure roller with a coating thickness of 2μm and dried to form a first coating. Among them, the I of carbon nanotubes (CNT) D / I G The ratio is 1.5.

[0053] Graphite, binder styrene-butadiene polymer and sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 97.3:1.5:1.2 to form a negative electrode slurry (solid content of 75wt%). The negative electrode slurry was coated on the first coating layer with a coating thickness of 50μm, dried at 110°C, and then cold pressed, cut and slit, and dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet.

[0054] Preparation of isolation membrane:

[0055] Alumina and polyvinylidene fluoride were mixed in a mass ratio of 90:10 and dissolved in deionized water to form a ceramic slurry with a solid content of 50wt%. The ceramic slurry was then evenly coated on one side of a porous substrate (polyethylene, thickness 7μm, average pore size 0.073μm, porosity 26%) using a micro-concave coating method, and dried to obtain a double-layer structure of a ceramic coating and a porous substrate, with a thickness of 50μm.

[0056] Polyvinylidene fluoride (PVDF) and polyacrylate were mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer slurry with a solid content of 50wt%. The polymer slurry was then evenly coated on both surfaces of the double-layer structure of the ceramic coating and the porous substrate by a micro-concave coating method, and then dried to obtain an isolation membrane, wherein the thickness of the single-layer coating formed by the polymer slurry was 2μm.

[0057] Preparation of electrolyte:

[0058] In a dry argon atmosphere glove box, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a mass ratio of EC:EMC:DEC=3:5:2, and then lithium salt LiPF6 was added. After mixing evenly, an electrolyte was obtained in which the concentration of LiPF6 was 1.15 mol / L.

[0059] Preparation of lithium-ion batteries:

[0060] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive electrode and the negative electrode to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer packaging aluminum plastic film, and after dehydration at 80°C, the above electrolyte is injected and packaged, and a lithium-ion battery is obtained through a process of formation, degassing, and trimming.

[0061] Other embodiments and comparative examples are based on the steps of embodiment 1 with parameter changes, and the specific changed parameters are as follows.

[0062] The thickness of the first coating layer in Examples 2 to 11 is different from that in Example 1, and the other parameters are the same as those in Example 1.

[0063] The thickness of the first coating in Examples 12 to 14 is different from that in Example 1, and a second coating is coated on the surface of the negative electrode active material layer, the second coating includes the same components as the first coating, the thickness of the second coating in Example 12 is 200nm, the thickness of the second coating in Example 13 is 450nm, the thickness of the second coating in Example 14 is 600nm, and the other parameters are the same as those in Example 1.

[0064] The thickness of the first coating in Examples 15 to 18 is different from that in Example 1, and the content of each component of the first coating is different from that in Example 1, and the other parameters are the same as those in Example 1. In Comparative Example 1, CNT is replaced with graphite, and the other parameters are the same as those in Example 1.

[0065] The following describes the testing methods for various parameters of the samples in the embodiments of the present application.

[0066] Carbon nanotube content test method:

[0067] This mass content can be obtained by quantitative thermogravimetric analysis (TG) based on the peak area to obtain the content ratio. The primer material is dried and placed in a high temperature resistant container, which is placed in a high temperature furnace with programmable temperature control, and the object to be tested is hung on a highly sensitive and accurate balance. During the heating or cooling process, the weight of the object to be tested changes due to the reaction, forming a relationship between the mass of the primer material and the temperature change, and the mass ratio is obtained based on the area of ​​the fitting peak.

[0068] Carbon nanotubes I D / I G Ratio test:

[0069] The surface defects of the samples were tested by laser confocal Raman spectrometer at 1350 cm -1 The peak intensity I D With 1580cm -1 The peak intensity I G The ratio I D / I G The value characterizes the surface defect of the sample. Each sample is tested with multiple potentials, and the standard deviation value characterizes the uniformity of the surface defect in different regions. D / I G The mean and standard deviation of I are obtained by taking unscreened carbon nanotubes and testing 100 points to obtain the corresponding I D / I G Calculate the mean and standard deviation of these 100 values.

[0070] Adhesion test:

[0071] The brand of the instrument used for the adhesion test is Instron, model 33652. Take the negative electrode sheet (width 30mm × length (100mm to 160mm)), fix it on the steel plate with double-sided tape (model: 3M9448A, width 20mm × length (90mm to 150mm)), fix a paper tape with the same width as the negative electrode sheet to one side of the negative electrode sheet with tape, adjust the limit block of the tensile testing machine to the appropriate position, fold the paper tape upward and slide 40mm, the sliding rate is 50mm / min, and test the adhesion of the negative electrode sheet at 180° (i.e. stretching in the opposite direction).

[0072] Shock test:

[0073] First, pre-treat the lithium-ion battery. The test temperature is 25℃±5℃. Charge to the full charge voltage with a current of 0.5C, and keep the voltage constant at 0.05C. Record the voltage and internal resistance before the test, and check the appearance. Then place the sample on a steel plate (thickness ≥5㎝), place the round bar in the center of the sample (round bar: φ15.8±0.1㎜), and test the wide side. Use a 9.1±0.1Kg hammer, 61±2.5cm from the intersection of the round bar and the sample, and drop it vertically in a free state. After falling, stop when the surface temperature of the lithium-ion battery rises by 10℃. (Stop the test after 5 minutes of data collection). After the test, check the appearance. The battery passes if it does not catch fire or explode.

[0074] Cycle performance test:

[0075] The test temperature is 25℃±2℃, charge at 0.7C constant current to full charge voltage, charge at constant voltage to 0.05C, and let stand for 5 minutes. Discharge at 0.5C to 3.0V. The capacity obtained in this step is taken as the initial capacity, and a cycle test is performed at 0.7C charge / 0.5C discharge. The capacity retention rate when the cycle is cycled to 800 times at 25℃ is recorded as the cycle performance of the lithium-ion battery.

[0076] DCR test process:

[0077] 1) Place in a -20℃ low temperature box for 4 hours;

[0078] 2) 0.7C (i.e. the current value that completely discharges the theoretical capacity within 1.6 hours) constant current charging to 4.35V, 4.35V constant voltage charging to 0.025C, sleep for 10 minutes;

[0079] 3) 0.1C discharge to 3.4V, sleep for 5 minutes (this step gets the actual capacity)

[0080] 25℃ DCR ​​test

[0081] 4) Sleep for 5 minutes, charge at 0.7C constant current to 4.35V, charge at 4.35V constant voltage to 0.025C (calculated using the actual capacity obtained in step 3)

[0082] 5) Sleep for 10 minutes;

[0083] 6) 0.1C discharge for 3h (using the actual capacity obtained in step 3 to calculate 70% SOC (remaining battery capacity) DCR)

[0084] 7) 1C discharge for 1s (5ms sampling, capacity is calculated based on the marked capacity of the corresponding battery pack)

[0085] 8) 0.1C discharge for 5h (calculated using the actual capacity obtained in step 3, 20% SOC DCR)

[0086] 9) 1C discharge for 1s (5ms sampling, capacity is calculated based on the marked capacity of the corresponding battery pack)

[0087] 10) Discharge at 0.1C for 1h (calculated using the actual capacity obtained in step 3 to obtain 10% SOC DCR).

[0088] Diaphragm resistance test:

[0089] 1) Use the four-probe method to test the film resistance;

[0090] 2) After the electrode coated with negative electrode slurry is cold pressed and placed in a 25°C environment for 1 day, it is placed on the platform of a four-probe resistivity tester.

[0091] 3) Adjust and fix the test sample, adjust the probe probe with the knob and press it against the sample surface

[0092] 4) Set the test conditions, including test voltage, current, probe spacing and other related data. The output of the result is resistance, and the resistance value can be measured.

[0093] Demolding test:

[0094] 1) 0.7C (i.e. the current value that completely discharges the theoretical capacity within 1.6h) constant current charge to 4.35V, 4.35V constant voltage charge to 0.025C, sleep for 10min;

[0095] 2) Place the lithium-ion battery in a low-humidity room and disassemble the negative electrode interface;

[0096] 3) Observe whether the negative electrode active material layer is separated from the first coating layer.

[0097] Deformation test:

[0098] 1) 0.7C (i.e. the current value that completely discharges the theoretical capacity within 1.6h) constant current charging to 4.35V, 4.35V constant voltage charging to 0.025C;

[0099] 2) Wrap the Ni tab of the lithium-ion battery with wrinkle glue to prevent external short circuit of the lithium-ion battery;

[0100] 3) Place the lithium-ion battery on the support pad under the 3D profilometer to measure the height of the concave and convex points, and run the VR-3000 measurement software for low-magnification fine measurement;

[0101] 4) Select a baseline to observe the deformation performance.

[0102] Table 1 shows various parameters and evaluation results of Examples 1 to 18 and Comparative Example 1.

[0103] Table 1

[0104]

[0105]

[0106] By comparing Example 1 and Comparative Example 1, it can be seen that by using carbon nanotubes in the first coating layer, the impact test pass rate can be significantly improved compared with conventional graphite.

[0107] By comparing Examples 1 to 11, it can be seen that when the thickness of the first coating is too small, the negative electrode sheet is easily peeled off. As the thickness of the first coating decreases, the bonding force of the negative electrode sheet also decreases, and the impact test pass rate also decreases, but the cycle performance of the electrochemical device tends to improve.

[0108] By comparing Example 9 and Examples 15 to 18, it can be seen that when the mass content of carbon nanotubes in the first coating is greater than 75%, film peeling and deformation after cycling will occur, and the cycle capacity retention rate will also drop rapidly. As the mass content of carbon nanotubes in the first coating increases, the impact test pass rate tends to decrease.

[0109] By comparing Example 9 and Examples 12 to 14, it can be seen that by forming an additional second coating on the surface of the negative electrode plate, the impact test pass rate can be further improved, and as the thickness of the second coating increases, the improvement effect is enhanced. However, when the thickness of the second coating is greater than 450nm, the cycle capacity retention rate will drop below 80%.

[0110] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. An electrochemical device comprising: A negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector, a first coating and a negative electrode active material layer, wherein the first coating is disposed between the negative electrode current collector and the negative electrode active material layer, The first coating layer comprises carbon nanotubes, a first binder and a first dispersant, and the mass content of the carbon nanotubes in the first coating layer is 50% to 75%; The diameter of the carbon nanotubes is 2 nm to 2000 nm. Under Raman spectroscopy, the carbon nanotubes have an I D / I G The ratio is greater than 1.

4.

2. The electrochemical device according to claim 1, wherein: The thickness of the first coating layer is 200 nm to 2 μm.

3. The electrochemical device according to claim 2, wherein: The thickness of the first coating layer is 800 nm to 1 μm.

4. The electrochemical device according to claim 1, further comprising a second coating layer, wherein the negative electrode active material layer is located between the first coating layer and the second coating layer, and the second coating layer comprises carbon nanotubes, wherein the mass content of the carbon nanotubes in the second coating layer is 50% to 75%.

5. The electrochemical device according to claim 4, wherein: The thickness of the second coating layer is greater than 0 and less than or equal to 450 nm.

6. The electrochemical device according to claim 4, wherein: The first binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyacrylate or polyacrylonitrile.

7. The electrochemical device according to claim 4, wherein: The first dispersant includes at least one of sodium hydroxymethyl cellulose, lithium hydroxymethyl cellulose or N-methyl pyrrolidone.

8. The electrochemical device according to claim 1, wherein The resistance of the negative electrode plate is 90mΩ to 1000mΩ.

9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Electrode coated with conductive carbon layer on surface and preparation method of electrode

    CN105895855A

  • Electrochemical device and electronic device

    CN113422063A